Statistical and economic analysis of solar radiation and climatic data for the development of solar PV system in Nigeria - Abdulkarim, Hauwa Talatu; Sansom, Christopher L.; Patchigolla, Kumar (Elsevier, 2020)
The growth in energy demand and global concern about the environment has resulted in the drive towards alternative energy sources and consequently this research concerning solar energy harvesting of radiation received at the earth’s surface. Analysis of solar radiation data is an important tool in the accurate designing/sizing of solar Photovoltaic (PV) systems and conducting performance analysis of the system. This paper presents the statistical and economic analysis of solar radiation and climatic data for the development of Solar PV systems in Nigeria. The data for three locations, one from each of the radiation regions in Nigeria were analysed using Minitab 17. The analysis shows that Maiduguri is more viable for solar energy conversion system than the two other locations, and for the same energy demand of 1.1MWh, the peak watt (Wp) of solar PV array required are 619419.27 Wp, 821142.52 Wp and 1219489.32 Wp for Maiduguri, Minna and Port Harcourt respectively. This leads to a difference of $460,984.72 in the total project cost between Maiduguri and Minna for the same energy demand.
Keywords: Analysis; Energy; Environment; Data; Nigeria; PV system